THE INFLUENCE OF THYROID DISORDERS ON CARDIOVASCULAR SYSTEM: CLINICAL CASE - G. A. Chervyakova; R. A. Sharipov (Российский кардиологический журнал)
Changes in the cardiovascular system are frequently put in the first place in the clinical picture of thyrotoxicosis while subclinical disease course is often neglected. Patients develop thyrotoxic cardiopathy which regresses in case of early detection and adequate treatment. It develops slowly in case of failure to recognize the syndrome of the disease. The article is a case study which illustrates a clinical course of an uncommon complication of thyrotoxicosis — conductivity disturbance which leads to atrioventricular obstruction